Navigating the challenges of a warmer climate: strategies for mitigating impacts and fostering resilience in India - Ravindra, K.; Bhardwaj, S.; Gandhi, A. P.; Attri, S. D.; Mor, S. (SAGE Publications, 2025)
The rising temperatures impact the environment, economy, public health, and global climate. This rise can be attributed to greenhouse gas emissions, urbanization, deforestation, and changes in oceanic currents. Higher temperatures pose a health risk and can result in dehydration and heat stroke while also affecting agricultural yields, aggravating water scarcity, increase in the frequency and intensity of hydroclimatic extreme weather events such as heatwaves, flooding, or droughts in different regions. Further, it can affect the construction, energy generation, and tourism industries. This paper highlights the fundamental factors behind the summer temperature rise in India and its impacts. The recommendations aim to improve the adaptation to the changes on individual and governmental levels. There is a need to encourage a carbon-neutral economy and tap into the resources for research and development of technologies. The paper also underscores the relationship between increased temperatures and the possibility of a pandemic in the future, as increased temperatures have the ability to change the pathogen behavior, and understanding the relationship between both is essential to formulate policies and future interventions.